Determinan Kinerja Keuangan Provinsi Gorontalo Tahun 2017-2022 - Dita Triyana Safitri Alhabsyi; Gaffar; Muhammad Ichsan Gaffar (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze the effect of Local Revenue, General Allocation Fund, General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund on the Financial Performance of Gorontalo Province Local Government. The data used in this study is secondary data sourced from the Directorate General of Balance of the Ministry of Finance of the Republic of Indonesia obtained from 6 regencies / cities in Gorontalo Province. This study uses Multiple Linear Regression Analysis of Panel data using the Fixed Effect Model (FEM). The results of this study indicate that 1). Regional Original Revenue has a positive and significant effect on Local Government Financial Performance, meaning that every increase in PAD by 1 rupiah can improve Regional Financial Performance. 2). The General Allocation Fund has a positive and significant effect on Regional Financial Performance, meaning that every increase in the General Allocation Fund by 1 rupiah can improve Regional Financial Performance. 3). The Special Allocation Fund has a positive and significant effect on Regional Financial Performance, meaning that any increase in the Special Allocation Fund by 1 rupiah can improve Regional Financial Performance. 4). Revenue Sharing Fund has a negative and significant effect on Regional Financial Performance, meaning that every increase in Revenue Sharing Fund of 1 rupiah can reduce Regional Financial Performance.